2014
DOI: 10.1016/j.annemergmed.2013.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Admit or Transfer? The Role of Insurance in High-Transfer-Rate Medical Conditions in the Emergency Department

Abstract: Insurance status appears to play a role in ED disposition (transfer versus admission) for many high-transfer conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 27 publications
4
51
2
Order By: Relevance
“…21 Our findings suggest that payer status, particularly lack of insurance, is likely to affect the care that pediatric patients receive in EDs and inpatient units. Similar findings have been documented among infants (aged 0 to 28 days) 12 and adults 8,10 : patients without insurance have been shown to have approximately 2 times the odds of transfer relative to patients with private insurance. Consistent with our results, those of a study of children with psychiatric-related ED visits demonstrated that patients with Medicaid were 10% more likely to be transferred compared with those with private insurance.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…21 Our findings suggest that payer status, particularly lack of insurance, is likely to affect the care that pediatric patients receive in EDs and inpatient units. Similar findings have been documented among infants (aged 0 to 28 days) 12 and adults 8,10 : patients without insurance have been shown to have approximately 2 times the odds of transfer relative to patients with private insurance. Consistent with our results, those of a study of children with psychiatric-related ED visits demonstrated that patients with Medicaid were 10% more likely to be transferred compared with those with private insurance.…”
Section: Discussionsupporting
confidence: 76%
“…Consistent with our results, those of a study of children with psychiatric-related ED visits demonstrated that patients with Medicaid were 10% more likely to be transferred compared with those with private insurance. 13 Patients without insurance, with Medicaid, and with other government insurance receive lower physician and hospital payments relative to those with private insurance, 8,[22][23][24] and it is likely for this reason that we observe a similar phenomenon in EDs caring for pediatric patients. This finding is consistent with those of studies demonstrating that physicians are often reluctant to accept or provide care to patients with insurance plans providing lower reimbursement.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Of note, these estimates were adjusted for comorbidity burden of the population, but not for acute illness severity. [8] A similar study specific to major trauma patients who initially presented to non-trauma emergency departments found that after adjustment for mechanism of injury and injury severity score, uninsured patients were more likely to be transferred to a trauma center whereas insured patients were more likely to be admitted to the non-trauma center. [6] This finding among trauma transfers was corroborated by evaluations of payer mix among head-injured patients using the National Trauma Data Bank (NTDB) and regional studies of trauma patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is notable that other studies have shown that Medicaid patients presenting to the emergency department are more likely to be transferred; however, this relationship may be influenced by the Emergency Medical Treatment and Labor Act, which mandates that acute care hospitals accept patients in transfer from emergency departments when a request has been issued for a higher level of care (38).…”
Section: Original Researchmentioning
confidence: 99%